Force Majeure and Credit Restructuring: A Doctrinal Perspective on the Resolution of Non-Performing Loans Caused by Natural Disasters - Tarmizi Tarmizi; Atika Sandra Dewi (APPTHI, 2025)
This study analyzes the legal relationship between force majeure and credit restructuring in Indonesia, particularly in addressing non-performing loans (NPLs) caused by natural disasters. It examines how force majeure is applied in credit agreements and how credit restructuring serves as a legal and financial mechanism to manage disaster-related credit distress. Using a doctrinal legal approach, the study reviews statutory provisions, banking regulations, and relevant literature, including Articles 1244 and 1245 of the Indonesian Civil Code and OJK Regulation No. 40/POJK.03/2019. The findings indicate that although Indonesian law recognizes natural disasters as potential force majeure events, their application in credit agreements is not automatic. Debtors must prove a direct causal link between the disaster and their inability to perform contractual obligations, which often leads to legal uncertainty and inconsistent interpretation. At the same time, credit restructuring, through rescheduling, reconditioning, and restructuring, provides a more practical response to financial distress. However, it operates separately from the force majeure doctrine, resulting in limited legal integration. The study also highlights that credit restructuring thus plays a dual role: supporting financial system stability and contributing to socio-economic recovery, particularly for micro, small, and medium enterprises.